Laser Nursing - A Perioperative Challenge - Smalley, Penny (Operating Room Nurses Association of Canada Journal, 1992)
Laser technology, once a dream of scientists and visionaries, has now become an accepted method of surgical and medical treatment in hospitals, clinics, and private offices, around the world. The technology has had an impact on every clinical discipline, including general surgery, otolaryngology, dermatology and plastic surgery, gynecology, neurosurgery, gastroenterology, urology, ophthalmology, podiatry, physical therapy and oncology.